(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The date palm Phoenix dactylifera L. is a very important economic crop in Iraq and some Arab countries. Date palm trees are infected with a large number of insect pests in all its parts, which leads to a decrease in the productivity of dates in terms of quality and quantity, including the lesser date moth Batrachedra amydraula Meyrick (Cosmopterygidae: Lepidoptera). This study was conducted to find out determine the incidence and population density of the lesser date moth B. amydraula on date palm cultivars sensitive to infection in Basra governorate (south of Iraq) on palm trees cultivars (Barhi, Sayer and Halawi), in Shatt Al-Arab area, Basra Governorate, during the 2018 season. The results showed that the highest infection rate for Barhi cultivar was in the first week of June, reaching 58.07%, while the highest infection rate was during the last week of May for Sayer cultivar and amounted to 63.21% which amounted to 67.23%. The results also showed that the highest population density of Lesser date moth B. amydraula larvae of Barhi cultivar reached 57.06 larvae/bunch during the month of June, while it reached for Sayer and Halawi cultivars (52.01 and 47.24 larvae/ bunch) respectively during the end of May.